Genetic diversity and distinction of Enterococcus faecium and Enterococcus lactis in traditional Montenegrin brine cheeses and salamis - Daza Prieto, Beatriz; Raicevic, Nadja; Martinovic, Aleksandra; Ladstätter, Johann; Zuber Bogdanovic, Ivana; Schorpp, Anika; Stoeger, Anna; Mach, Robert L.; Ruppitsch, Werner; Cabal, Adriana (Frontiers in Microbiology, 2024)
IntroductionEnterococcus faecium is a widespread acid-lactic bacterium found in the environment, humans, and animal microbiota, and it also plays a role in the production of traditional food. However, the worldwide emergence of multidrug-resistant E. faecium strains represents a major public health threat and is the primary reason that the genus Enterococcus is not recommended for the Qualified Presumption of Safety (QPS) list of the European Food Safety Authority (EFSA), raising concerns about its presence in food products.MethodsIn this study, 39 E. faecium and 5 E. lactis isolates were obtained from artisanal brine cheeses and dry sausages, sourced from 21 different Montenegrin producers. The isolates were collected following the ISO 15214:1998 international method and processed for whole-genome sequencing (WGS).ResultsGenome analysis based on core genome multilocus sequence type (cgMLST) revealed a high diversity among isolates. Furthermore, the isolates carried antimicrobial resistance genes; the virulence genes acm, sgrA, and ecbA; the bacteriocin genes Enterolysin A, Enterocin A, Enterocin P, Duracin Q, Enterocin B, Bacteriocin 31, Enterocin EJ97, Sactipeptides, and Enterocin SEK4; the secondary metabolite genes T3PKS, cyclic lactone autoinducer, RiPP-like, and NRPS and a maximum of eight plasmids.ConclusionThis study highlights the need for careful monitoring of E. faecium and E. lactis strains in food to ensure they do not pose any potential risks to consumer safety.